Women's Economic Empowerment Through Sharia Principles - Maghfiroha, Anisatul (Nursyam Center, 2024)
This research explores women's economic empowerment through the application of sharia principles. Women's economic empowerment is a strategic step in achieving the welfare of the family and society as a whole. Sharia principles offer an ethical and fair approach to managing economic resources, which includes justice, transparency, and social responsibility. This study examines various empowerment models based on sharia principles, such as microfinance programs, sharia cooperatives, and entrepreneurship education in accordance with Islamic values. This research method uses a qualitative method. The results of the study show that the application of sharia principles in women's economic empowerment can improve economic welfare, strengthen family resilience, and encourage women's active participation in economic activities. Thus, sharia principles can be a strong basis for women's economic empowerment programs in various social and cultural contexts.